Shoaling in eyed and blind morphs of the characin Astyanax fasciatus under light and dark conditions - Gregson, J; De Perera, T (2007)
The shoaling behaviour of the visual, epigean morph of the characin Astyanax fasciatus was found to be quantitatively different from the blind, hypogean morph. © 2007 The Fisheries Society of the British Isles.